2016
DOI: 10.1111/hir.12160
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell research: the role of information seeking and scanning

Abstract: Acquiring stem cell research information, both intentionally and unintentionally, is positively related to stem cell research knowledge and perspectives. Future research should further identify ways to promote health information acquisition behaviour because it is associated with better knowledge and more positive opinion formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Twenty-four of these papers related specifically to cell therapy while 11 pertained to gene therapy. Five of the included studies were conducted in the UK [12][13][14][15][16] , eight in the USA [17][18][19][20][21][22][23][24] , six in Canada [25][26][27][28][29][30] , two were conducted in Australia 31,32 and one each from Belgium 33 , China 34 , Germany 35 , Hungary 36 , Ireland 37 , Japan 38 , Korea 39 , South Korea 40 and Sweden 41 . One study included multiple countries across Europe 42 , three studies were set in Canada and USA [43][44][45] and one included Europe, USA and Canada 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four of these papers related specifically to cell therapy while 11 pertained to gene therapy. Five of the included studies were conducted in the UK [12][13][14][15][16] , eight in the USA [17][18][19][20][21][22][23][24] , six in Canada [25][26][27][28][29][30] , two were conducted in Australia 31,32 and one each from Belgium 33 , China 34 , Germany 35 , Hungary 36 , Ireland 37 , Japan 38 , Korea 39 , South Korea 40 and Sweden 41 . One study included multiple countries across Europe 42 , three studies were set in Canada and USA [43][44][45] and one included Europe, USA and Canada 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge and understanding of cell and gene therapies. The studies reported varying levels of patient knowledge and understanding of cell and gene therapies 13,19,23,31,33,40,41 . Studies in patients with ischaemic stroke, cystic fibrosis and sickle cell anaemia found that they had limited prior knowledge of cell and gene therapy 13,23,40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…The impact of information, or lack of access to information, were issues of concern in studies conducted by Nelissen et al . and Rose et al .…”
Section: In This Issue…mentioning
confidence: 99%
“…In their standardised cross‐sectional survey of 621 cancer‐diagnosed and 1387 non‐diagnosed individuals, Nelissen et al. investigated patterns of knowledge acquisition and its impact on knowledge and perspectives of stem cell research . Similar view points were expressed by both populations concerning societal benefit, research evaluation and morality with the acquisition of information, both intentional and unintentional, positively related to stem cell knowledge and perspectives.…”
Section: In This Issue…mentioning
confidence: 99%
See 1 more Smart Citation